It may not be the smartest thing to do, but sometimes it`s the only option: a longitudinal mixed-methods study of analgesic use in youth elite athletes - Pedersen, J. R.; Storm, L. K.; Larsen, A. C.; Møller, M.; Koes, B.; Mohammednejad, A.; Thorlund, J. B. (Journal of Orthopaedic & Sports Physical Therapy, 2025)
OBJECTIVES: To (1) compare analgesic use over 36 weeks between endurance athletes, technical athletes, and team athletes, and (2) explore experiences and sociocultural factors impacting analgesic use.